Allosterically Regulated Phosphatase Activity from Peptide–PNA Conjugates Folded Through Hybridization. (20th June 2016) - Machida, Takuya; Dutt, Som; Winssinger, Nicolas
Abstract: The importance of spatial organization in short peptide catalysts is well recognized. We synthesized and screened a library of peptides flanked by peptide nucleic acids (PNAs) such that the peptide would be constrained in a hairpin loop upon hybridization. A screen for phosphatase activity led to the discovery of a catalyst with >25‐fold rate acceleration over the linear peptide. We demonstrated that the hybridization‐enforced folding of the peptide is necessary for activity, and designed a catalyst that is allosterically controlled using a complementary PNA sequence.